The prognostic significance of early blood neurofilament light chain concentration and magnetic resonance imaging variables in relapse‐onset multiple sclerosis - Williams, Thomas; Heslegrave, Amanda; Zetterberg, Henrik; Miszkiel, Katherine A; Barkhof, Frederik; Ciccarelli, Olga; Brownlee, Wallace J; Chataway, Jeremy (Brain and behavior, 2022)
Background Improved prognostication remains vital in multiple sclerosis to inform personalized treatment approaches. Blood neurofilament light (bNfL) is a promising prognostic biomarker, but to what extent it provides additional information, independent of established MRI metrics, is yet to be established. Methods We obtained all available bNfL data for 133 patients from a longitudinal observational cohort study. Patients were dichotomized into good or poor outcome groups based upon clinical and cognitive assessments performed 15 years after a clinically isolated syndrome. We performed longitudinal modeling of early NfL and MRI variables to examine differences between outcome groups. Results The bNfL dataset was incomplete, with one to three (mean 1.5) samples available per participant. Within 3 months of onset, bNfL was similar between groups. The bNfL concentration subsequently decreased in those with a good outcome, and remained persistently elevated in those with a poor outcome. By year 5, NfL in the poor outcome group was approximately double that of those with a good outcome (14.58 [10.40–18.77] vs. 7.71 [6.39–9.04] pg/ml, respectively). Differences were reduced after adjustment for longitudinal changes in T2LV, but trends persisted for a greater rate of increase in NfL in those with a poor outcome, independent of T2LV. Conclusions This analysis requires replication in cohorts with more complete bNfL datasets, but suggests that persistently elevated blood NfL may be more common in patients with a poor long‐term outcome. Persistent elevation of blood NfL may provide additional prognostic information not wholly accounted for by standard monitoring techniques.